2000
DOI: 10.1007/s002160050036
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cadmium by flow injection-chemical vapor generation-atomic absorption spectrometry

Abstract: A method was developed for the generation of a "cold vapor" of cadmium by means of flow injectionchemical vapor generation from aqueous samples, the determination being conducted with an atomic absorption spectrometer (Pyrex glass T-cell). Several gas-liquid separator designs, atomizer designs, and the effect of several reagents previously reported as sensitivity enhancers (including cobalt, nickel, thiourea and didodecyl-dimethylammonium bromide) were investigated. The limit of detection, calculated as the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 23 publications
1
49
0
1
Order By: Relevance
“…The glass beads prevented liquid transfer to the atomizer and by submerging the GLS in the ice-bath, carry-over of water vapor following the heating step was further minimized. It is possible that other designs of GLS would be suitable; however, previous studies [39] have shown that the best design may be dependent on the analyte and operating conditions.…”
Section: Flow-injection Manifoldmentioning
confidence: 99%
“…The glass beads prevented liquid transfer to the atomizer and by submerging the GLS in the ice-bath, carry-over of water vapor following the heating step was further minimized. It is possible that other designs of GLS would be suitable; however, previous studies [39] have shown that the best design may be dependent on the analyte and operating conditions.…”
Section: Flow-injection Manifoldmentioning
confidence: 99%
“…However, the many different chemical properties of hydrido metal complexes, in addition to those of free atoms and nanoparticles, serve as a basis for explanations of such complex results observed during CVG as the memory effects, the acid-base behaviour observed during rinsing experiments, the effect of added surfactant and other additives as well as many other observations noted in the present and previous studies. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]43 …”
Section: ð22þmentioning
confidence: 99%
“…Existem, na literatura, inúmeras aplicações da técnica de geração de hidretos com detecção por espectrometria atômica, em uma ampla variedade de amostras: alimentos (As) [163][164][165][166] ; água (As) 6,[167][168][169][170][171][172] , (Pb) 173 , (Sn) 174 , (Sb) [175][176][177] , (Se) [178][179][180] , (Tl) 181 , (As e Se) 182 , (As, Se e Sb) 183 , (As, Se, Sb e Ge) 184 ; água e solo (Pb) 185 , amostras ambientais (As) 186 , (Cd) 187 , (Sb) 188,189 , (Sn) 190 ; amostras biológicas (Se) 7 , (As e Bi) 191 ; amostras biológicas e ambientais (As) 192 , (Cd) 193 , (As e Se) 194 ; amostras clíni-cas: cabelo (Se) 195 , (Sb) 196 , urina (As) [197][198][199][200][201] , (Bi) 202 , (Se) 203,205 ; bebidas: vinho (Sb) 206 , vinho e cerveja (As) 207<...>…”
Section: Aplicaçõesunclassified